2022
DOI: 10.3390/molecules27051482
|View full text |Cite
|
Sign up to set email alerts
|

Novel Complex of PD-L1 Aptamer and Albumin Enhances Antitumor Efficacy In Vivo

Abstract: The PD-1/PD-L1 pathway blockade can generate a good clinical response by reducing immunosuppression and provoking durable antitumor immunity. In addition to antibodies, aptamers can also block the interaction between PD-1 and PD-L1. For the in vivo application, however, free aptamers are usually too small in size and quickly removed from blood via glomerular filtration. To avoid renal clearance of aptamer, we conjugated the PD-L1 aptamer to albumin to form a larger complex (BSA-Apt) and evaluated whether BSA-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…MP7-PEG suppressed tumor growth in PD-L1 + colon carcinoma cells in C57Bl/6 mice. An et al coupled BSA through succinyl-maleimide chemistry, as in Figure A, to a sulfur-modified PD-L1 aptamer (5′-SH-TTTTTTACGG­GCCACATCAA­CTCATTGATA­GACAATGCGT­CCACTGCCCGT-3′) with close to 60% efficacy using an aptamer:BSA ratio of 5:1 . The particle size (11.6 nm) was expected to limit kidney clearance, and binding of the anti-PD-L1 aptamer to the CT26 cell line was maintained after its modification.…”
Section: Pre-clinical Applications With Pd-1/pd-l1 Aptamersmentioning
confidence: 99%
“…MP7-PEG suppressed tumor growth in PD-L1 + colon carcinoma cells in C57Bl/6 mice. An et al coupled BSA through succinyl-maleimide chemistry, as in Figure A, to a sulfur-modified PD-L1 aptamer (5′-SH-TTTTTTACGG­GCCACATCAA­CTCATTGATA­GACAATGCGT­CCACTGCCCGT-3′) with close to 60% efficacy using an aptamer:BSA ratio of 5:1 . The particle size (11.6 nm) was expected to limit kidney clearance, and binding of the anti-PD-L1 aptamer to the CT26 cell line was maintained after its modification.…”
Section: Pre-clinical Applications With Pd-1/pd-l1 Aptamersmentioning
confidence: 99%
“…Lai et al developed a high-affinity aptamer for human PD-L1 [ 15 ]. Several studies have demonstrated that this aptamer generates good antitumor efficacy in preclinical researches [ 16 , 17 ], indicating that the PD-L1 aptamer has potential for clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since their discovery, DNA or RNA-based aptamers have been designed to act against a wide variety of targets present on the surface of cells, ranging from small molecules [1,2], oligonucleotides [3,4], peptides [5][6][7], to complex proteins [8][9][10]. DNA/RNA aptamers have been incredibly useful in biomedical applications, such as biosensing [11,12], biomarker discovery [13,14], medical imaging [15][16][17], and drug delivery [18,19].…”
Section: Introductionmentioning
confidence: 99%